Analysis of the Impact of Leadership Change Utilizing Leader–Member Exchange (LMX) Initiatives on Employee Engagement - Anggraini, Diska Asri (AIBPM Publisher, 2025)
This study investigates how a leadership transition affects employee engagement at PT XY Indonesia, with a focus on the quality of leader–employee relationships during periods of organizational change. Leadership transitions often bring uncertainty, which can influence how employees connect with and adapt to new leadership approaches. The research applies the Leader–Member Exchange (LMX) theory, which highlights the role of trust, respect, and mutual obligation in leader–follower relationships. Adopting a qualitative case study approach, this study aims to capture in-depth employee perspectives and experiences following a change in top leadership. The findings are expected to provide practical insights into how relational leadership can sustain or enhance employee engagement during change. This research is particularly relevant for human resource professionals and leaders seeking to support workforce morale, commitment, and motivation in the face of transitions, and to understand the relational strategies that can help employees remain engaged throughout periods of organizational adjustment.